2007
DOI: 10.1017/cbo9780511497384
|View full text |Cite
|
Sign up to set email alerts
|

The Spoils of Partition

Abstract: The partition of India in 1947 was a seminal event of the twentieth century. Much has been written about the Punjab and the creation of West Pakistan; by contrast, little is known about the partition of Bengal. This remarkable book by an acknowledged expert on the subject assesses the social, economic and political consequences of partition. Using compelling sources, the book, which was originally published in 2007, shows how and why the borders were redrawn, how the creation of new nation states led to unprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 212 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…115 Therefore, despite the apparent geographical absurdity of their territorial claim, the Hindu Mahasabha argued on their behalf before the Boundary Commission. 116 Even the Congress memorandum to the Boundary Commission listed these territories among the areas it claimed for West Bengal on the ground of being non-Muslim 'contiguous majority areas', a criterion followed by the commission for the apportionment of territories. 117 On the other side of the spectrum, Jinnah accosted the viceroy in June 1947 with the proposal of a referendum for Bengal, 'to give the Scheduled Castes the chance of expressing their dissatisfaction with caste Hindus'; but the viceroy 'refused to be drawn' into any such discussion.…”
Section: Towards Partitionmentioning
confidence: 99%
“…115 Therefore, despite the apparent geographical absurdity of their territorial claim, the Hindu Mahasabha argued on their behalf before the Boundary Commission. 116 Even the Congress memorandum to the Boundary Commission listed these territories among the areas it claimed for West Bengal on the ground of being non-Muslim 'contiguous majority areas', a criterion followed by the commission for the apportionment of territories. 117 On the other side of the spectrum, Jinnah accosted the viceroy in June 1947 with the proposal of a referendum for Bengal, 'to give the Scheduled Castes the chance of expressing their dissatisfaction with caste Hindus'; but the viceroy 'refused to be drawn' into any such discussion.…”
Section: Towards Partitionmentioning
confidence: 99%
“…52 Most have either clung on precariously where they were, albeit in ever-shrinking spaces, or have been displaced to areas within West Bengal where more of their fellow Muslims live in densely concentrated and economically depressed clusters. 53 For these Bengali Muslims, "staying on" in India has meant a rapid downward spiral in prosperity, status, and security. Decades of communist government notwithstanding, they are among the most impoverished communities in the region.…”
Section: S T a Y I N G O N : G H E T T O I Z At I O N A M O N G " N Amentioning
confidence: 99%
“…69 With respect to West Bengal in this period, Joya Chatterji has shown that 'the spoils of partition' were distributed among sections of the state elite and upwardly mobile castes and commercial groups, which changed the balance of power and wealth within that society. 70 The chief refugee 'gainers' from the scheme of redistribution of evacuee property in Pakistan were urban migrants who took over the industries and businesses vacated by Hindus and Sikhs, many of which had grown considerably in areas of West Punjab and Karachi during the Second World War. These migrants were largely drawn from Gujaratispeaking Khoja and Memon refugee communities from Kathiawar and Bombay.…”
Section: Refugee Corruptionmentioning
confidence: 99%